Pembinaan Keagamaan di SMAN Taruna Madani Bangil: Upaya Penguatan Karakter Religius Siswa - Solehudin, Muhamad; Nurhanifansyah, Nurhanifansyah; Ali, Muhamad Najib; Husni, Zidan Muhtadin (Al Mu'azarah: Jurnal Pengabdian Kepada Masyarakat, 2025)
This community engagement program analyzes the transformation of SMAN 1 Bangil into SMAN 1 Taruna Madani in Pasuruan Regency, a collaboration between the East Java Provincial Government, the Indonesian Navy (TNI AL), and Pondok Pesantren Darullughah Wadda’wah (Dalwa). The initiative focuses on the integration of academic education, discipline training, and religious values, and their impact on students' character development. Using the Participatory Action Research (PAR) method, data was collected through in-depth interviews, participatory observation, program documentation, and open-ended questionnaires. The results show significant improvements in religious awareness, discipline, and social responsibility, with students demonstrating better time management between academic, religious, and social obligations. Activities such as congregational prayers, Quran memorization, and religious studies enhanced students' spiritual values, while discipline training by TNI AL built responsibility and resilience. Social programs like community service and environmental campaigns cultivated empathy and social engagement among students. Despite these successes, challenges remain in curriculum integration, infrastructure readiness, and educator training. Recommendations include enhancing coordination among stakeholders, accelerating infrastructure development, and providing continuous training for educators and instructors. This integrated education model is expected to serve as a sustainable reference for similar schools in fostering disciplined, responsible, and spiritually aware students.